The carrying capacity for the development of marine ecotourism - Ilham Junaid; Andi Nur Fauziah (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Tanjung Karang in Donggala Regency has the potential to be developed using the concept of marine ecotourism. However, the management system tends to be contradictory with the principles of marine ecotourism. The aim of this research is to understand the supporting factors and challenges in implementing marine ecotourism in Tanjung Karang, as well as studying the carrying capacity and human resources. A qualitative research method was used through interviews and participant observation. The research shows that natural potential and traditional socio-cultural activities conducted by the community are both essential in supporting Tanjung Karang as a channel of marine ecotourism. The three management systems supported by the community, government and private sector are capable of making a diﬀerence in relation to marine ecotourism implementation. In building tourism facilities, people tend to ignore the environmental preservation aspect. In addition, the private sector, as one of the tourism developers, also needs to ensure the management of Tanjung Karang that they will provide opportunities for the local community to enjoy nature and the culture oﬀered. This tourism should not be exclusively for international tourists. Although Tanjung Karang has been used as a tourist attraction before, marine ecotourism has not been prioritised as the development framework by the stakeholders. Eﬀorts have been undertaken to support the implementation of marine ecotourism and the stakeholder needs to understand the supporting factors and challenges involved, as well as the carrying capacity, in order to develop Tanjung Karang's marine ecotourism.